2019
DOI: 10.1186/s12887-019-1687-0
|View full text |Cite
|
Sign up to set email alerts
|

Echocardiography-guided percutaneous closure of perimembranous ventricular septal defects without arterial access and fluoroscopy

Abstract: Background: Traditional percutaneous device closure of perimembranous ventricular septal defects (PmVSDs) is a minimally invasive technique, but can result in high radiation exposure and can result in potential arterial complications. Here, we aimed to assess the safety and feasibility of device closure of PmVSDs via the femoral vein approach under transesophageal echocardiography (TEE) guidance in children. Methods: From January 2014 to December 2017, a total of 46 PmVSD patients (mean age, 6.5 ± 2.3 years [r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
1
7

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 25 publications
0
11
1
7
Order By: Relevance
“…Unlike the whole instrument-tracking images from fluoroscopy, echocardiography images are segmental; therefore, an arterio-venous loop is difficult to establish using a snare. A single vessel is routinely employed in such instances [14,15]. Wang et al have demonstrated the feasibility and safety of the retrograde approach through the femoral artery under TTE guidance alone.…”
Section: Discussionmentioning
confidence: 99%
“…Unlike the whole instrument-tracking images from fluoroscopy, echocardiography images are segmental; therefore, an arterio-venous loop is difficult to establish using a snare. A single vessel is routinely employed in such instances [14,15]. Wang et al have demonstrated the feasibility and safety of the retrograde approach through the femoral artery under TTE guidance alone.…”
Section: Discussionmentioning
confidence: 99%
“…Adicionalmente, se seleccionaron 16 series de casos [86][87][88][89][90][91][92][93][94][95][96][97][98][99][100][101] para hacer un análisis descriptivo de la seguridad del uso de dispositivos o de la cirugía estándar y que ha aportado una población de estudio adicional de 2940 pacientes.…”
Section: Perforación Cardíacaunclassified
“…Todas las series de casos incorporan pacientes con CIV perimembranosa y en 7 de ellas, incluyen también población con CIV muscular [87][88][89][90][91]94,95 . Una de las series de casos aporta 400 pacientes intervenidos mediante cirugía estándar 87 y una segunda serie de casos, 235 pacientes intervenidos mediante cierre perventricular 98 .…”
Section: Perforación Cardíacaunclassified
“…Congenital heart disease (CHD) is currently the common type of congenital malformation in infants [4,5], and PAH presents with unique features in this disease. In these patients, the arteriopathy is triggered by increased pulmonary blood flow resulting from a left-to-right shunt due to intracardiac or extracardiac defect.…”
Section: Introductionmentioning
confidence: 99%